2016
DOI: 10.1007/s00775-016-1370-y
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase and catechol oxidase activity of copper(I) complexes supported by imidazole-based ligands: structure–reactivity correlations

Abstract: Four new imidazole-based ligands, 4-((1H-imidazol-4-yl)methyl)-2-phenyl-4,5-dihydrooxyzole (L OL 1), 4-((1H-imidazol-4-yl)methyl)-2-(tert-butyl)-4,5-dihydrooxyzole (L OL 2), 4-((1H-imidazol-4-yl)methyl)-2-methyl-4,5-dihydrooxyzole (L OL 3), and N-(2,2-dimethylpropylidene)-2-(1-trityl-1H-imidazol-4-yl-)ethyl amine (L imz 1), have been synthesized. The corresponding copper(I) complexes [Cu(I)(L OL 1)(CH3CN)]PF6 (CuL OL 1), [Cu(I)(L OL 2)(CH3CN)]PF6 (CuL OL 2), [Cu(I)(L OL 3)(CH3CN)]PF6 (CuL OL 3), [Cu(I)(L imz 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 69 publications
(96 reference statements)
4
25
0
5
Order By: Relevance
“…Deprotonation of L H2 ·2HCl to give the catechol L H2 is achieved with [(nBu) 4 N]OH. Compound L H2 is soluble in protic solvents like CH 3 OH, but insoluble in polar aprotics olvents such as CH 3 [26][27][28] The UV/Vis spectra of L in CH 3 OH solutions display transitions at 268, 369, and 559 nm ( Figure S3). According to DFT calculations, an isolated L H2 molecule exists in its catechol form rather than in its possible zwitterionic protomers, in which one, respectively two protons are transferred from the hydroxy groups to the imino N atomso fg uanidino groups.T he DFT calculations (B3LYP/def2-TZVPP)p redict these protomers to be 75/80 kJ mol À1 (two isomers for one protonated guanidino group) respectively 235 kJ mol À1 higher in energy ( Figure S2).…”
Section: Ligand Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Deprotonation of L H2 ·2HCl to give the catechol L H2 is achieved with [(nBu) 4 N]OH. Compound L H2 is soluble in protic solvents like CH 3 OH, but insoluble in polar aprotics olvents such as CH 3 [26][27][28] The UV/Vis spectra of L in CH 3 OH solutions display transitions at 268, 369, and 559 nm ( Figure S3). According to DFT calculations, an isolated L H2 molecule exists in its catechol form rather than in its possible zwitterionic protomers, in which one, respectively two protons are transferred from the hydroxy groups to the imino N atomso fg uanidino groups.T he DFT calculations (B3LYP/def2-TZVPP)p redict these protomers to be 75/80 kJ mol À1 (two isomers for one protonated guanidino group) respectively 235 kJ mol À1 higher in energy ( Figure S2).…”
Section: Ligand Synthesis and Characterizationmentioning
confidence: 99%
“…logue reaction of catecholt og ive o-benzoquinone. [26][27][28] The UV/Vis spectra of L in CH 3 OH solutions display transitions at 268, 369, and 559 nm ( Figure S3). In CH 3 CN, the lowest-energetic transition (p HOMO !p* LUMO according to time-dependent DFT calculations, see MO in Supporting Information, Figure S5) is blueshifted to 539 nm, and the 372 nm (intramolecular CT p G !p* LUMO and p HOMO-2 !p* LUMO )a nd 278 nm (intramolecular CT p HOMO !p* G )t ransitions are redshifted( Figures S3, S6).…”
Section: Ligand Synthesis and Characterizationmentioning
confidence: 99%
“…[1,2] Die katalytische Oxidation von Catecholen und p-Hydrochinon mit O 2 wurde mit zweikernigen wie auch einkernigen Übergangsmetallkomplexen (vor allem Kupfer, Cobalt und Eisen) als Katalysatoren detailliert untersucht. [3][4][5][6][7] Stahl, Hammes-Schiffer et al klärten die Mechanismen solcher Reaktionen auf und gruppierten Chinone in zwei Familien:s olche mit hohen Redoxpotentialen wie 2,3-Dichlor-5,6-dicyan-1,4-benzochinon (DDQ) und bioinspirierte o-Chinone,d ie dem o-Chinon-Cofaktor ähneln, in Aminoxidasen sowie verwandten Enzymen vorkommen und niedrigere Redoxpotentiale aufweisen. [7,8] Spezielle o-Chinone ermçgli-chen die aerobe Oxidation von Aminen ohne die Notwendigkeit eines Metallkatalysators.…”
Section: Die Katalytisches Elektiveunclassified
“…[6][7][8] Recently, attention has turned to Cu(I) complexes in terms of their abilities to mimic catecholase oxidase.Ramadanet al, reported Cu(I) and Cu(II) complexes of a new tetradentate Schiff-base containing N 4 donors and found out that the Cu(I) gave the highest turnover rate. 9 Also a number of new copper(I) complexes functioning as model systems for tyrosinase have been reported [10][11][12] ,even though Cu(II) complexes still receive far greater attention in this field amongst other metal ions.…”
Section: Introductionmentioning
confidence: 99%